2005
DOI: 10.1177/194589240501900206
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Effects of Pentachlorophenol, Lindane, Transfluthrin, Cyfluthrin, and Natural Pyrethrum on Human Mucosal Cells of the Inferior and Middle Nasal Conchae

Abstract: Our study strongly suggests that exposure to PCP, lindane, transfluthrin, cyfluthrin, and natural pyrethrum has a genotoxic effect on the epithelial cells of human nasal mucosa. In addition, we have shown that nasal structures differ in susceptibility to the various pesticides used in the tests. Thus, the study provides new evidence supporting the biological plausibility of PCP- and lindane-induced effects, thereby helping evaluate potential PCP- and lindane-induced mucous membrane carcinomas of these parts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…In the case presented here, we describe a subject developing permanent anosmia, preceded by nasal irritation and short lasting phantosmia and torqosmia, after working several hours in a room treated with an insecticide sprayed to control infestation of parasites. cells of human nasal mucosa has been observed [37]. These studies lend support to the hypothesis of the insecticide exposure as the primary cause for the permanent anosmia observed.…”
Section: Ijomeh 2012;25(4)supporting
confidence: 74%
“…In the case presented here, we describe a subject developing permanent anosmia, preceded by nasal irritation and short lasting phantosmia and torqosmia, after working several hours in a room treated with an insecticide sprayed to control infestation of parasites. cells of human nasal mucosa has been observed [37]. These studies lend support to the hypothesis of the insecticide exposure as the primary cause for the permanent anosmia observed.…”
Section: Ijomeh 2012;25(4)supporting
confidence: 74%
“…The genotoxic and/or cytotoxic potential of some Type II pyrethroid insecticides such as cyfluthrin [Tisch et al, 2005], cypermethrin [Amer and Aboul-Ela, 1985;Bhunya and Pati, 1988;Amer et al, 1993;Chauhan et al, 1997Chauhan et al, , 1999Hadnagy et al, 1999;Institóris et al, 1999;Giri et al, 2003;Patel et al, 2006;Suman et al, 2006], deltamethrin [Agarwal et al, 1994;Surrallés et al, 1995;Gandhi et al, 1995;Villarini et al, 1998], fenvalerate [Pati and Bhunya, 1989;Puig et al, 1989;Surrallés et al, 1990;Caballo et al, 1992;Ghosh et al, 1992;Giri et al, 2002], and k-cyhalothrin [Campana et al, 1999;Ç elik et al, 2003, 2005a, 2005bNaravaneni and Jamil, 2005] has been shown in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that PCE/NCE ratio decreased in tetramethrine group showed that the chemical affected the bone marrow cells. In parallel to results of the study conducted on the genotoxicity of pesticides in pyrethroide group [28,[30][31][32]. This study concluded that tetramethrine had a genotoxic effect; however, it had a limited effect depending on dosage.…”
Section: Discussionmentioning
confidence: 67%
“…In the study conducted by Tisch et al, to investigate the effect of transfluthrin in the mucosa cells of human nasal cavity, they determined that transfluthrin had a genotoxic effect [30]. Institoris et al, examined the genotoxic effects of permethrin on the bone marrow cells of male winstar rats and identified that numerical chromosome abnormalities increased in all the dosages used [31].…”
Section: Discussionmentioning
confidence: 99%